2019
DOI: 10.1002/asia.201900963
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Preparation of Large‐Sized Rings of Single‐Stranded DNA through One‐Pot Ligation of Multiple Fragments

Abstract: Circular single‐stranded DNA (c‐ssDNA) has significant applications in DNA detection, the development of nucleic acid medicine, and DNA nanotechnology because it shows highly unique features in mobility, dynamics, and topology. However, in most cases, the efficiency of c‐ssDNA preparation is very low because polymeric byproducts are easily formed due to intermolecular reaction. Herein, we report a one‐pot ligation method to efficiently prepare large c‐ssDNA. By ligating several short fragments of linear single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…In the “simple one‐pot strategy” in Scheme 1A, [11] however, all the short ssDNA fragments and the splints are added into a reaction vessel at the beginning of reaction. With this method, the reaction never proceeds in a stoichiometric fashion, and the amounts of target rings produced are limited, as described below.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the “simple one‐pot strategy” in Scheme 1A, [11] however, all the short ssDNA fragments and the splints are added into a reaction vessel at the beginning of reaction. With this method, the reaction never proceeds in a stoichiometric fashion, and the amounts of target rings produced are limited, as described below.…”
Section: Resultsmentioning
confidence: 99%
“…In order to produce large c‐ssDNAs more easily without size‐limitation, we recently developed an alternative strategy in which multiple short linear ssDNA fragments (30–60 nt) as starting materials are convergently connected and cyclized in situ to c‐ssDNA (Scheme 1A) [11] . In a reaction vessel, all of these short fragments were mixed with all the splints before the treatment with T4 DNA ligase.…”
Section: Introductionmentioning
confidence: 99%
“…At present, researchers have significantly improved the circularization efficiency by reducing MgCl 2 concentration [31], using the terminal hairpin of the ssDNA substrate [32] or frozen/lyophilization/cyclization (FLC) [33]. Sui et al reported a one-pot ligation method to efficiently prepare longer circular ssDNA (>90 nt) [34], but several splints were needed, and the yield was not high enough in some cases. In our new approach presented here, each ssDNA circle was synthesized by using two fragments, which could hybridize with each other to form two nicks (Figure 2A).…”
Section: Preparation Of Circular Ssdna By Two Dna Hairpinsmentioning
confidence: 99%
“…Recently, we have successfully prepared stable non-modified Z-DNA (LR-chimera involving the left-handed part and the right-handed one) under physiological ionic conditions (e.g., 10 mM MgCl 2 ) using two complementary 74~111 bp long circular single-stranded DNA (ssDNA) [30]. The circularization of ssDNA is a critical step, which needs to be improved [31][32][33][34]. In addition, the LR-chimera we prepared is difficult to attach onto the surface of the probe, because it has no ssDNA part for further hybridization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation